Hello, love, goodbye a feminist critical discourse analysis on the representation of filipina migrant workers in popular filipino film - Yu, Rozhelle Sophia L. (2023)
Film uses its discourse to communicate crucial information to a wide audience, allow for the discussion of past knowledge, and contribute to the development of new knowledge, which also has the potential to regulate or question already-existing societal systems. With this, I addressed the representation of Filipina migrant workers in Filipino-made films. Critically analyzing how the abuse and realities that this marginalized group continuously face in their line of work are being represented in popular films that involve the narratives of people from this group specifically. At the same time, paying close attention to the involvement of the societal institutions and structures of class, labor, and migration that all have gendered-centered nuances around them in the narrative as well. Through the use of a Feminist Critical Discourse Analysis (FCDA), the oppressive systems, harmful ideologies, and unbalanced nature of the power dynamics within the film Hello, Love, Goodbye were uncovered. This revealed the common themes of (1) Asymmetric Relations between Filipina Migrant Workers and Everyone Else, (2) Female Migrant Workers as Transnational Mothers, (3) Filipina Migrant Workers as Passive Subjects to the Dominant Group, (4) The Labor Conditions of Filipina Migrant Workers, (5) The Role of Hello, Love, Goodbye as a Medium, and (6) Normalizing Oppressive System that was heavily utilized in the film. These findings helped enhance understanding regarding the intricate multilayered interactions among gender, power, and ideology in film discourse and the political economy of Filipino films in general.